(untitled) (Research, Society and Development, 2023)
Introduction: Physical inactivity is neglecting children and adolescents, in view of this, it causes psychomotor delays along with behavioral changes and psychological damage resulting from a sedentary lifestyle and the loss of children’s and youth games due to the use of technologies by children and adolescents. Objective: to reiterate, through a bibliographic review, physical exercise as a means of psychomotor intervention for the cognitive, biomechanical and physiological performance of children and adolescents to promote good habits and behaviors throughout life. Justification: In this way, how does physical exercise contribute to a means of intervention in the motor development of children and adolescents? Physical training is of paramount importance for children and adolescents, it promotes benefits in physical fitness and psychomotor pillars in favor of essential physical conditioning and quality of life, to make adults and elderly healthy in their biological age in the future. Methodology: This study is a narrative review, as according to Oliveira et al. (2022) narrative reviews are characterized as an understanding and analysis of a particular subject of literature that present narratives already effectively published. In this study, the bibliographical references selected and used in the research were published and indexed works taking into account the period from 2009 to 2022. Final considerations: In the present study, knowledge was coordinated regarding the importance of practicing physical exercise since childhood and the main problems related to physical inactivity. In view of this, we can state that psychomotricity linked to physical exercise is of paramount importance for the development of motor, cognitive, biomechanical and physiological skills of the human being.